Internet promotion of agroforestry networks within regional development planning - Andreopoulou Z.; Kalfagianni A. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Agroforestry is the combination of trees, crops and livestock on the same area and it applies to all agricultural systems. Agroforestry activities can have a positive socio-economic impact to regional sustainable development and planning, especially in the Mediterranean where it constitutes a traditional practice. Internet promotion can play a critical role in planning strategies for regional development. The aim of this paper is to identify and retrieve Internet websites that promote agroforestry issues and to study their content characteristics. Additionally we propose a model website structure with a user-friendly environment aiming to promote agroforestry for Mediterranean areas supporting all the necessary information concerning socio-economic benefits. Through the proposed website structure, local populations can be motivated as to the preservation of agroforest ecosystems and their services and contribute to local socio-economic activities.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)